Barriers and facilitators to healthcare utilization amongst people living with sickle cell disease in the United States: A scoping review - Christina Ruan; Joyce Gyamfi; Nana Osei-Tutu; Shreya Meda; Lydia Samuels; Nousheen Inayat; Sukruthi Thunga; Elizabeth Noble; Dorice L. Viera; Deborah Adenikinju; Charmaine Royal; Angela Odoms-Young; et al. (PLoS ONE, 2026)
Background Sickle cell disease (SCD) stands as one of the most prevalent genetic disorders in the United States (U.S.) that causes severe consequences such as organ damage and excruciating pain. Alarmingly, recent literature indicates a decline in the number of people living with SCD (PLWSCD) seeking professional care – hinting at an avoidance of the healthcare system. Therefore, this scoping review synthesizes the evidence regarding barriers and facilitators influencing healthcare utilization among PLWSCD within the U.S. Methods To map the current literature on SCD management and provide a comprehensive overview of the current knowledge gaps regarding healthcare utilization for PLWSCD, a scoping review was conducted. A systematic search of articles reporting on the utilization of healthcare among PLWSCD in the U.S using seven data sources was conducted on March 24, 2023, without any restrictions on publication date and language. To capture any additional articles, the search was updated on March 4, 2024. Two reviewers independently assessed studies for inclusion, data extraction, and risk of bias (RoB). Main results A total of 708 articles were screened; 70 met the study criteria. Results indicated that the four most common barriers were social ( n = 25) interpersonal ( n = 23), economic ( n = 15), and institutional level factors ( n = 11). The top four most common facilitators were technology ( n = 9), education ( n = 7), autonomy ( n = 6), and a positive patient-provider relationship ( n = 6). The most common forms of healthcare utilization were inpatient or hospital admissions ( n = 19) and emergency department (ED) visits ( n = 18). Evidence-based interventions (EBI) found to decrease healthcare avoidance included individualized pain plans (IPPs) ( n = 4) and quality improvement (QI) strategies ( n = 3). Conclusion This scoping review identified complex multilevel barriers that impede healthcare utilization, and facilitators likely to promote healthcare utilization among PLWSCD in the U.S. Future research should prioritize developing and evaluating comprehensive, multi-level interventions that address identified barriers while leveraging facilitators to improve healthcare engagement and outcomes for this vulnerable population. Healthcare systems and health policies must urgently adopt and integrate evidence-based strategies to rebuild trust and ensure equitable, accessible care for PLWSCD.